Is There a Metamaterial Route to High Temperature Superconductivity? - Igor I. Smolyaninov; Vera N. Smolyaninova (Advances in Condensed Matter Physics)
Superconducting properties of a material such as electron-electron interactions and the critical temperature of superconducting transition can be expressed via the effective dielectric response function εeff (q,ω) of the material. Such a description is valid on the spatial scales below the superconducting coherence length (the size of the Cooper pair), which equals ∼100 nm in a typical BCS superconductor. Searching for natural materials exhibiting larger electron-electron interactions constitutes a traditional approach to high temperature superconductivity research. Here we point out that recently developed field of electromagnetic metamaterials deals with somewhat related task of dielectric response engineering on sub-100 nm scale. We argue that the metamaterial approach to dielectric response engineering may considerably increase the critical temperature of a composite superconductor-dielectric metamaterial.